Match observations in the Arctic winter 1996/97: High stratospheric ozone loss rates correlate with low temperatures deep inside the polar vortex - Schulz, Astrid; Rex, Markus; Steger, J.; Harris, N. R. P.; Braathen, G. O.; Reimer, E.; Alfier, R.; Beck, A.; Alpers, M.; Cisneros, J.; Claude, H.; De Backer, H.; et al. (2000)
With the Match technique, which is based on the coordinated release of ozonesondes, chemicalozone loss rates in the Arctic stratospheric vortex in early 1997 have been quantified in a verticalregion between 400K and 550K. Ozone destruction was observed from mid February to midMarch in most of these levels, with maximum loss rates between 25 and 45ppbv/day. The vortexaveraged loss rates and the accumulated vertically integrated ozone loss have been smaller than inthe previous two winters, indicating that the record low ozone columns observed in spring 1997were partly caused by dynamical effects. The observed ozone loss is inhomogeneous through thevortex with the highest loss rates located in the vortex centre, coinciding with the lowesttemperatures. Here the loss rates per sunlit hour reached 6 ppbv/h, while the correspondingvortex averaged rates did not exceed 3.9 ppbv/h.